CA-MRSA Decolonization Strategies: Do They Reduce Recurrence Rate?. Issue 6 (November 2016) - Tidwell, Joling; Kirk, Lisa; Luttrell, Tim; Pike, Caitlin A.
Abstract : BACKGROUND: Community-associated methicillin-resistant Staphylococcus aureus commonly presents as a skin and soft tissue infection. Recurrence of the infection is common even after incision and drainage of the affected area. OBJECTIVE: This Evidence-Based Report Card reviews whether decolonization strategies will reduce the rate of methicillin-resistant Staphylococcus aureus skin and soft tissue infection (MRSA-SSTI) recurrence or colonization in patients with a history of MRSA-SSTI. METHODS: A systematic review of the literature was conducted from 1987 to the present day. The studies that were evaluated included individuals with recurrent skin and soft tissue infections that used decolonization procedures to decrease recurrence. The literature search generated 754 articles. Of these, 288 articles were eliminated due to duplication. Of the 466 remaining citations, 372 were not relevant. Of the remaining 94 full-text articles, 12 met the inclusion criteria. These studies were then reviewed and findings synthesized. FINDINGS: Four studies found topical decolonization procedures were effective in reducing colonization rates. Of the studies that used combination decolonization therapy, 3 of 4 studies showed a decrease in colonization rate. Despite successful decolonization, the rate of SSTI recurrence did not decrease. Two studies that showed a decrease in SSTI recurrence utilized different study parameters. In one study, the decolonization regimen was completed monthly over 1 year. The other study treated family members in addition to the affected individual. Currently, there is insufficient evidence to support the routine use of topical or systemic decolonization regimens to decrease recurrent SSTIs in individuals with a history of MRSA-SSTI. CONCLUSION: The focus of decolonization should be focused on the prevention and spread of infection. Hygiene education should be provided to patients, household members, and close contacts to reduce infection rates.